Characterization of spatial Schmidt modes in high-gain SU(1,1) interferometers - Scharwald, Dennis; Sharapova, Polina (Physical Review Research)
Multimode quantum light has promising applications in many areas of physics, such as quantum communications and quantum computing. However, its multimode nature also makes it challenging to measure its properties. Recently [I. Barakat et al., Optica Quantum 3, 36 (2025)], a technique for the simultaneous measurement of squeezing of multiple broadband modes based on a phase-sensitive amplification approach was experimentally implemented using a setup that effectively corresponds to an SU(1,1) interferometer. Here, we aim to provide a complete theoretical analysis of the modal structure of (generally unbalanced) SU(1,1) interferometers and a detailed theoretical formal derivation of the framework for this technique. Utilizing the joint Schmidt decomposition of the transfer functions, we investigate the shape and phase profiles of the modes of the SU(1,1) interferometer and its components [parametric down-conversion (PDC) sections] for different parametric gain regimes. We discover a complicated interplay between the PDC modes and the modes of the entire interferometer, and analyze it by using their overlap coefficients as a similarity measure. Finally, we develop a rigorous processing method for the aforementioned multimode squeezing measurement technique and discuss necessary approximations to make this method experimentally feasible.

An applied noise model for scintillation-based CCD detectors in transmission electron microscopy - Zietlow, Christian; Lindner, Jörg K. N. (Scientific Reports)

An applied noise model for low-loss EELS maps - Lindner, Jörg K. N.; Zietlow, Christian (Ultramicroscopy)

From belonging to success: Evaluating the influence of sense of belonging to physics on first-year university students’ academic outcomes and the benefits of a holistic support program - Feser, Markus Sebastian; Bauer, Anna Brigitte (European Journal of Physics)
Abstract The present study explored the role of first-year physics students’ sense of belonging to physics and how it relates to their learning progression in higher education-level physics. Conducted at Paderborn University, this study examined how students’ sense of belonging to physics influences their academic outcomes in an introductory experimental physics course. Additionally, we investigated how physics students’ engagement in the Physiktreff—a holistic support program for first-year physics students to help them cope with academic and social challenges during their studies—impacts the development of their sense of belonging to physics over time. Our findings indicated that students with a stronger sense of belonging to physics performed better academically. Moreover, students who actively participated in the support program experienced a positive shift in their sense of belonging to physics. However, our findings also revealed that physics students with a higher initial sense of belonging to physics tended to experience a decline in their sense of belonging to physics during their first semester. These results underscore the importance of fostering a sense of belonging to physics within higher education, particularly during the introductory phase of students’ studies.

Strukturanalysen des physikdidaktischen Wissens mithilfe von Machine Learning - Zeller, Jannis
Das Fachdidaktische Wissen (FDW) zählt zu den zentralen Elementen des Professionswissens (angehender) Lehrkräfte und seine Relevanz ist sowohl theoretisch angenommen als auch empirisch belegt. In der fachdidaktischen Forschung liegt daher bereits seit längerem ein Fokus auf der Analyse des FDW, wobei mittlerweile vor allem Auswirkungen auf die Handlungsqualität und auf Lernergebnisse in den Blick genommen werden. Nach wie vor stellt aber auch die empirisch fundierte inhaltliche Beschreibung des FDW sowie der Transfer entwickelter FDW-Testverfahren auf Basis von Testinstrumenten mit offenem Antwortformat in die Ausbildungspraxis ein Forschungsdesiderat dar. In diesem Dissertationsprojekt werden daher auf Basis eines Datensatzes von 846 Bearbeitungen eines FDW-Testinstruments im Fach Physik (1) projektübergreifende FDW-Kompetenzniveaus auf Basis von Item-Response-Modellierungen exploriert, (2) nicht-hierarchische FDW-Kompetenzprofile auf Basis von (probabilistischen) Cluster- und Textanalysen beschrieben und (3) ein vollständig automatisiertes FDW-Assessment-System auf Basis von Machine Learning entwickelt. Dabei wurden insbesondere kognitive Anforderungskategorien als Subskalen des verwendeten Testinstruments betrachtet. Das Assessment-System wurde dabei auf Basis dieser und weiterer Subskalen sowie anhand der Zuordnung von Proband:innen zu den Kompetenzprofilen evaluiert und zeigte sowohl relativ zur Interrater-Übereinstimmung als auch absolut betrachtet hohe Performanzwerte.

"Heute wissen wir, wie das Universum aussieht!" ...oder? Eine digitale Lernumgebung zur Vorläufigkeit von naturwissenschaftlichem Wissen am Beispiel der Geschichte der Astronomie - Cramer, Katja; Webersen, Yvonne (MNU-Journal)

Enhancement Of Light-matter Interaction In Topological Waveguides And Resonators - Brauckmann, Michael; Narvaez Castaneda, Emmanuel; Siebert, Dustin; Brecht, Benjamin; Förstner, Jens; Zentgraf, Thomas (Proceedings of The 15th International Conference on Metamaterials, Photonic Crystals and Plasmonics)

Electro-optic frequency shift of single photons from a quantum dot - Kapoor, Sanjay; Rodek, Aleksander; Mikołajczyk, Michał; Szuniewicz, Jerzy; Sośnicki, Filip Maksymilian; Kazimierczuk, Tomasz; Kossacki, Piotr; Karpiński, Michał (Nanophotonics)
Quantum dots (QDs) are a promising source of single photons mainly due to their on-demand operation. However, their emission wavelength depends on their size and immediate surroundings in the solid-state environment. By applying a serrodyne electro-optic phase modulation, we achieve a spectral shift up to 0.01 nm (3.5 GHz) while preserving the purity and indistinguishability of the photons. This method provides an efficient and scalable approach for tuning the emission wavelength of QDs without relying on nonlinear frequency mixing or probabilistic processes. Our results show that the electro-optic phase modulation enables stable and tunable spectral shifts, making it suitable for applications such as quantum communication, quantum key distribution, and primarily integrating remote quantum dot sources into large-scale quantum networks.

Aberration-optimized electro-optic time lens model using a tunable aperture - Kapoor, Sanjay; Sośnicki, Filip Maksymilian; Karpiński, Michał (APL Photonics)
Time lenses have been recognized as crucial components for manipulating ultrafast optical pulses in various applications, from ultrafast spectroscopy to the interfacing of optical quantum systems. A time lens is characterized by its chirp rate, which determines the focusing strength of the time lens, and accurate knowledge of this chirp is critical for precise dispersion compensation and minimizing aberrations. Here, we introduce a tunable time aperture model for sinusoidal time lenses that provides a more accurate estimate of the effective chirp rate without modifying the device. We derive a closed-form expression for the maximum phase error and show how it depends on the time aperture. We experimentally demonstrate a 1.6-fold improvement in spectral bandwidth compression of Gaussian pulses compared to the conventional approach. Our framework offers a practical tool for designing efficient temporal optical systems, benefiting applications in both classical and quantum optics where accurate spectro-temporal shaping is essential.

Schmidt modes carrying orbital angular momentum generated by cascaded systems pumped with Laguerre–Gaussian beams - Scharwald, Dennis; Gehse, Lucas; Sharapova, Polina (APL Photonics)
Orbital angular momentum (OAM) modes are an important resource used in various branches of quantum science and technology due to their unique helical structure and countably infinite basis. Generating light that simultaneously carries high-order orbital angular momenta and exhibits quantum correlations is a challenging task. In this work, we present a theoretical approach to the generation of correlated Schmidt modes carrying OAM via parametric down-conversion (PDC) in cascaded nonlinear systems (nonlinear interferometers) pumped by Laguerre–Gaussian beams. We demonstrate how the number of generated modes and their population can be controlled by varying the pump parameters, the gain of the PDC process, and the distance between the crystals. We investigate the angular displacement measurement uncertainty of these interferometers and demonstrate that it can overcome the classical shot noise limit.

An applied noise model for scintillation-based CCD detectors in transmission electron microscopy. - Zietlow, Christian; Lindner, Jörg (Sci Rep)

An unbiased ADMM-TGV algorithm for the deconvolution of STEM-EELS maps - Zietlow, Christian; Lindner, Jörg (Ultramicroscopy)

A novel Lagrangian-based method for the deconvolution of electron energy-loss spectra - Zietlow, Christian
Electron energy-loss spectroscopy (EELS) is an advanced analytical technique in transmission electron microscopy, as it provides insights into material characteristics, such as electronic properties or elemental composition, at the atomic scale. The precision of every EELS analysis, however, is inherently limited by noises and blur. This thesis offers a comprehensive understanding of the noise, which is particularly valuable at low dwell times necessary for beam sensitive materials and for electron-matter interactions with low frequency of occurrence, where the noise dominates the measurement. Additionally, correlations encountered in the noise of an EELS measurement are described from both a theoretical and experimental perspective. These correlations are caused by a convolution of the noisy signal with the detector point spread function. Methods for characterizing key noise parameters of typical detectors are described, allowing the noise model to be tailored to any EELS detector. Ultimately, a novel deconvolution method enabling significant sharpening and denoising of EELS measurements is introduced and demonstrated. Its efficiency is further validated on both simulation and experimental data. The described advancement offered by the proposed deconvolution method enables the extension of current electron microscope capabilities, facilitating analysis that would be unfeasible with existing deconvolution techniques.

Simultaneous measurement of multimode squeezing through multimode phase-sensitive amplification - Barakat, Ismail; Kalash, Mahmoud; Scharwald, Dennis; Sharapova, Polina; Lindlein, Norbert; Chekhova, Maria (Optica Quantum)
Multimode squeezed light is an increasingly popular tool in photonic quantum technologies, including sensing, imaging, and computation. Meanwhile, the existing methods of its characterization are technically complicated, which reduces the level of squeezing, and mostly deal with a single mode at a time. Here, for the first time, to the best of our knowledge, we employ optical parametric amplification to characterize multiple squeezing eigenmodes simultaneously. We retrieve the shapes and squeezing degrees of all modes at once through direct detection followed by modal decomposition. This method is tolerant to inefficient detection and does not require a local oscillator. For a spectrally and spatially multimode squeezed vacuum, we characterize eight strongest spatial modes, obtaining squeezing and anti-squeezing values of up to −5.2 ± 0.2 dB and 8.6 ± 0.3 dB, respectively, despite the 50% detection loss. This work, being the first exploration of an optical parametric amplifier’s multimode capability for squeezing detection, paves the way for the real-time detection of multimode squeezing.

Boosting third-order nonlinearities in rutile TiO2 by chromium doping - Brinkmann, Marius; Meier, Falco; Spedt, Vladimir; Meier, Cedrik (Optics Express)
In this study, we investigate the impact of chromium-induced point defects on the nonlinear optical properties and electric-field-induced second harmonic generation (EFISH) in rutile titanium dioxide (TiO 2 ). Chromium thin films were deposited by electron beam evaporation on (001)-oriented bulk TiO 2 substrates and subsequently diffused into the lattice in a tube furnace under a nitrogen atmosphere at 900 °C. The introduction of chromium significantly enhanced the third harmonic generation (THG) of a 1560 nm laser, with an amplification factor of up to 8.3, indicative of an enhanced third-order nonlinear susceptibility, χ (3) . Moreover, the application of an external voltage induced a pronounced EFISH signal in the chromium-doped samples, further confirming the enhanced nonlinear response. These results demonstrate that defect engineering via chromium doping in rutile TiO 2 offers a promising pathway for the development of high-performance nonlinear optical devices.

Protecting physics students from pseudoscience - combining strategies for a comprehensive teaching approach - Webersen, Yvonne; Riese, Josef (European Journal of Physics)
Abstract Given the presence of fake news and pseudoscience (often disguised as physics), the importance of inoculating citizens against this type of misinformation has gained increasing attention in education. This is a goal that all subjects should pursue equally from their respective disciplinary perspectives. The paper presents a teaching approach to protect physics students from misinformation and pseudoscience by combining these three common strategies: First, understanding the fundamental principles of the Nature of Science. Second, identifying techniques of Science Denial. And third, applying heuristics for evaluating (supposedly) scientific information. Finally, the paper offers practical suggestions for applying these strategies in a master's-level physics course, using examples from the field of physics.

Entanglement between dependent degrees of freedom: Quasiparticle correlations - Barkhausen, Franziska; Ares Santos, Laura; Schumacher, Stefan; Sperling, Jan (Physical Review A)

Numerical solution of nonlinear Schrödinger equation by a hybrid pseudospectral-variational quantum algorithm - Köcher, Nikolas; Rose, Hendrik; Bharadwaj, Sachin S.; Schumacher, Jörg; Schumacher, Stefan (Scientific Reports)
Abstract The time-dependent one-dimensional nonlinear Schrödinger equation (NLSE) is solved numerically by a hybrid pseudospectral-variational quantum algorithm that connects a pseudospectral step for the Hamiltonian term with a variational step for the nonlinear term. The Hamiltonian term is treated as an integrating factor by forward and backward Fourier transforms, which are here carried out classically. This split allows us to avoid higher-order time integration schemes, to apply a first-order explicit time stepping for the remaining nonlinear NLSE term in a variational algorithm block, and thus to avoid numerical instabilities. We demonstrate that the analytical solution is reproduced with a small root mean square error for a long time interval over which a nonlinear soliton propagates significantly forward in space while keeping its shape. We analyze the accuracy and complexity of the quantum algorithm, the expressibility of the ansatz circuit and compare it with classical approaches. Furthermore, we investigate the influence of algorithm parameters on the accuracy of the results, including the temporal step width and the depth of the quantum circuit.

Optically and remotely controlling localization of exciton-polariton condensates in a potential lattice - Ai, Qiang; Wingenbach, Jan; Yang, Xinmiao; Wei, Jing; Hatzopoulos, Zaharias; Savvidis, Pavlos G.; Schumacher, Stefan; Ma, Xuekai; Gao, Tingge (Physical Review Applied)

Demonstration of domain wall current in MgO-doped lithium niobate single crystals up to 400°C - Wulfmeier, Hendrik; Yakhnevych, Uliana; Boekhoff, Cornelius; Diima, Allan; Kunzner, Marlo; Verhoff, Leonard M.; Paul, Jonas; Ratzenberger, Julius; Beyreuther, Elke; Gössel, Joshua; Kiseleva, Iuliia; Rüsing, Michael; et al. (Solid State Ionics)
Conductive ferroelectric domain walls (DWs) represent a promising topical system for the development of nanoelectronic components and device sensors to be operational at elevated temperatures. DWs show very different properties as compared to their hosting bulk crystal, in particular with respect to the high local electrical conductivity. The objective of this work is to demonstrate DW conductivity up to temperatures as high as 400 °C which extends previous studies significantly. Experimental investigation of the DW conductivity of charged, inclined DWs is performed using 5 mol % MgO-doped lithium niobate single crystals. Current–voltage ( ) curves are determined by DC electrometer measurements and impedance spectroscopy and found to be identical. Moreover, impedance spectroscopy enables to recognize artifacts such as damaged electrodes. Temperature dependent measurements over repeated heating cycles reveal two distinct thermal activation energies for a given DW, with the higher of the activation energies only measured at higher temperatures. Depending on the specific sample, the higher activation energy is found above 160 °C to 230 °C. This suggests, in turn, that more than one type of defect/polaron is involved, and that the dominant transport mechanism changes with increasing temperature. First principles atomistic modeling suggests that the conductivity of inclined domain walls cannot be solely explained by the formation of a 2D carrier gas and must be supported by hopping processes. This holds true even at temperatures as high as 400 °C. Our investigations underline the potential to extend DW current based nanoelectronic and sensor applications even into the so-far unexplored temperature range up to 400 °C.